Social, nutritional, and behavioral aspects associated with erosive tooth wear - considerations and preventive aspects (Research, Society and Development, 2021)
Erosive tooth wear is a multifactorial condition resulting from the loss of mineralized dental structure by chemical, physical and / or mechanical processes, in the absence of microorganisms (biofilm), being modulated by biological, behavioral and occupational factors. The increase in the prevalence of non-carious tooth wear is mainly related to changes in eating habits, lifestyle and behavior in the last three decades, which has been cause for concern by the dental community. Due to the increase in life expectancy, especially in more developed countries, maintaining oral health is essential to improve quality of life and prevent comorbidities, increase self-esteem, in addition to improving chewing, speech and social life. Currently, the diagnosis of erosive tooth wear is based on clinical aspects of the lesions, however, knowing the factors associated with nutrition, occupation and lifestyle are essential to define the risk and the susceptibility of the patient to the development of lesions and indication of preventive measures and control. In view of the increase in its incidence and prevalence in young adults, the dental surgeon must know about its etiology, prevention, and treatment. Still, public policies focused on this issue need to be created and adopted. Thus, this study describes the main etiological, nutritional, behavioral, and social aspects associated with non-carious tooth wear, offering important information regarding treatment and mainly prevention.